A Review of Solvate Ionic Liquids: Physical Parameters and Synthetic Applications - Eyckens, Daniel J.; Henderson, Luke C. (Frontiers in Chemistry, 2019)
Solvate Ionic Liquids (SILs) are a relatively new class of ionic liquids consisting of a coordinating solvent and salt, that give rise to a chelate complex with very similar properties to ionic liquids. Herein is the exploration of the reported Kamlet-Taft parameters, Gutmann Acceptor numbers and the investigation of chelating effects through NMR spectroscopy of multiple atomic nuclei. These properties are related to the application of SILs as reaction media for organic reactions. This area is also reviewed here, including the implication in catalysis for the Aldol and Kabachnik-Fields reactions and electrocyclization reactions such as Diels-Alder and [2+2] cycloaddition. Solvate ILs exhibit many interesting properties and hold great potential as a solvent for organic transformations.